MOTIF DAN KEPUASAN PENDENGAR SIARAN MUTIARA KALBU DI RADIO PRADYA SUARA FM TUBAN - Irawatiningrum, Satya (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
Radio Pradya Suara, which broadcasts on the FM 94.6 Mhz, has one of the programs, namely Mutiara Kalbu which is broadcast from 17.00 to 18.00 every Monday-Friday. This program is intended as a medium of Islamic preaching for its listeners, which has a 55% adult audience segmentation. Preaching through radio media to convey everything about Islam is necessary to be developed in order to reach a wider audience. Because radio is still in demand among the people of Tuban Regency, especially among rural areas. In addition, radio has advantages that other mass media do no have, namely proximity to the audience. The purpose of this research is to find out the motives and satisfaction of listeners of Mutiara Kalbu broadcast program on Radio Pradya Suara FM. While in practice using quantitative methods with regression data analysis techniques. Respondents in this study were 65 listeners of Pradya Suara FM radio and the result is motive greatly influenced listener satisfaction of Mutiara Kalbu broadcast program on Radio Pradya Suara FM.